Diagnostic accuracy of narrow‐band imaging endoscopy with targeted biopsies compared with standard endoscopy with random biopsies in patients with Barrett's esophagus: A systematic review and meta‐analysis. Issue 10 (5th July 2021) - Hajelssedig, Omer Eljyli; Zorron Cheng Tao Pu, Leonardo; Thompson, Jacqueline Y; Lord, Anton; El Sayed, Iman; Meyer, Chase; Shaukat Ali, Faisal; Abdulazeem, Hebatullah M; Kheir, Ammar O; Siepmann, Timo; Singh, Rajvinder
Abstract: Background and Aim: Endoscopic surveillance for dysplasia in Barrett's esophagus (BE) with random biopsies is the primary diagnostic tool for monitoring clinical progression into esophageal adenocarcinoma. As an alternative, narrow‐band imaging (NBI) endoscopy offers targeted biopsies that can improve dysplasia detection. This study aimed to evaluate NBI‐guided targeted biopsies' diagnostic accuracy for detecting dysplasia in patients undergoing endoscopic BE surveillance compared with the widely used Seattle protocol. Methods: Cochrane DTA Register, MEDLINE/PubMed, EMBASE, OpenGrey, and bibliographies of identified papers were searched until 2018. Two independent investigators resolved discrepancies by consensus, study selection, data extraction, and quality assessment. Data on sensitivity, specificity, and predictive values were pooled and analyzed using a random‐effects model. Results: Of 9528 identified articles, six studies comprising 493 participants were eligible for quantitative synthesis. NBI‐targeted biopsy showed high diagnostic accuracy in detection of dysplasia in BE with a sensitivity of 76% (95% confidence interval [CI]: 0.61–0.91), specificity of 99% (95% CI: 0.99–1.00), positive predictive value of 97% (95% CI: 0.96–0.99), and negative predictive value of 84% (95% CI: 0.69–0.99) for detection of all grades of dysplasia. The receiver‐operating characteristic curve for NBI model performance was 0.8550 for detecting all dysplasia. Conclusion: Narrow‐band imaging‐guided biopsy demonstrated high diagnostic accuracy and might constitute a valid substitute for random biopsies during endoscopic surveillance for dysplasia in BE.